Potential Benefits of Ethanol extract of Anredera cordifolia for Antiobesity of High Fat diet-Induced Obesity in White Male Rat Wistar (Baghdad Science Journal, 2024)
Obesity-related deaths continue to rise, and thus losing weight in overweight and obese patients is critical to prevent complications. Anredera cordifolia (Ten,) Steenis, species of succulent plant of the genus Basellaceae, is widely used in herbal medicine to decrease body weight. This study evaluated the potential benefits of Anredera cordifolia ethanol extract to reduce body weight in high-fat diet-induced obesity rat model. This was an experimental with post-test only control group design study involving 36 obese rats. They were divided into two groups: three control groups (K1, K2, K3) and three treatment groups (P1, P2, P3). All the groups were induced with high-fat diet, except K1 control group that received a standard diet. K2 group received no treatment, and K3 group was given orlistat. Whereas, treatment group received Anredera cordifolia ethanol extract at different dose, such as 50 mg/kg BW (P1), 100 mg/kg BW (P2), and 150 mg/kg BW (P3). After 4 weeks of treatment, all groups of rats were sacrificed. ERK levels and PPARγ in abdominal visceral adipose tissue were measured using ELISA and immunohistochemistry. Body weight and abdominal circumference were measured through anthropometric examination. Weight loss was observed in the groups that received 100 and 150 mg/kg BW Anredera cordifolia ethanol extract, followed by the decrease in ERK levels and PPAR expression. Ethanol extract of Anredera cordifolia used as an antiobesity in this study decreased PPARγ transcription factor and reduced ERK levels to inhibit adipogenesis.